Fatigue life estimation based on fracture mechanics of single spot welded joints under different loading modes. (15th April 2017) - Tanegashima, Ryota; Akebono, Hiroyuki; Sugeta, Atsushi
Highlights: The fatigue properties of single spot welded joints strongly depend on the loading mode. In shear- and peel-type joints, cracks initiate in the thickness direction. Conventional theories cannot be used to predict the fatigue properties of the joints. Experimentally and numerically obtained crack initiation angles were in good agreement. The effects of the loading mode on the fatigue properties of the joints can be evaluated by Δ K I, θmax . Abstract: To evaluate the accuracy of joint fatigue life estimations obtained using conventional theories, the fatigue properties of shear- and peel-type single spot welded joints were investigated experimentally and analytically. The observed crack initiation angles differed from the predictions obtained using conventional theories, indicating that the theories cannot be used to evaluate the fatigue properties of the joints. In contrast, the present analytical crack initiation angles were in good agreement with the experimental results. Therefore, the effect of the loading mode on the fatigue properties of the single spot welded joints was adequately determined from the range Δ K I, θ max of initial stress intensity factors thorough an analytical evaluation.